Elder Self-neglect and Suicidal Ideation in an U.S. Chinese Aging Population: Findings From the PINE Study - Dong, XinQi (J Gerontol A Biol Sci Med Sci, 2017)
BACKGROUND: Self-neglect and suicidal ideations are important public health issues among the aging population. This study aims to examine the association between self-neglect, its phenotypes, and suicidal ideation among U.S. Chinese older adults. METHODS: Guided by a community-based participatory research approach, the Population Study of Chinese Elderly in Chicago (PINE) study is a population-based epidemiological study conducted from 2011 to 2013 among 3,159 Chinese older adults aged 60 years and older in the Greater Chicago area. Self-neglect was assessed by a 27-item instrument, describing five phenotypes with hoarding, poor personal hygiene, unsanitary condition, lack of utilities, and need of home repair. Suicidal ideation was assessed by the ninth item of the Patient Health Questionnaire-9 (PHQ-9) and the Geriatric Mental State Examination-Version A (GMS-A). Logistic regression is utilized to analyze the association. RESULTS: Higher level of self-neglect was found significantly associated with increased risk of self-reported suicidal ideation within 2 weeks (odds ratio 2.97 [1.54–5.72]); 12 months (odds ratio 2.82 [1.77–4.51]); and lifetime (odds ratio 2.74 [1.89–3.95]). For phenotypes, the study found that poorer personal hygiene and severer level of unsanitary conditions were associated with increased risk of suicidal ideation at all three time periods. CONCLUSION: This study suggests that self-neglect and its phenotypes are significantly associated with suicidal ideation among Chinese older adults. Longitudinal studies are needed to explore the mechanisms through which self-neglect links with suicidal ideation.